Effects of exogenous progesterone on the ovine serum progesterone profile during the non-breeding season - Barati, F; Hosseini, P; Azari, M (Journal of the Hellenic Veterinary Medical Society, 2024)
Exogenous progesterone (PRG) sources are used to induce ovine estrus during the non-breeding season. Intramuscular injection (IM) of PRG is an uncommon route for this purpose. This study investigated serum progesterone (P4) levels after IM administration of 50 mg of two different PRG products. Ten ewes were selected and received two consecutive PGF2α injections at 24-h intervals. Serum samples were collected (Time 0), followed by the injection of single doses of Fertigest® or Vetagesterone®. Serum P4 levels were assayed at times (T) 0, 30 min, 3,6,12,24,48,72,96, and 120 h after injection. A large variation in the serum P4 levels at T0 was detected. The serum P4 level at T0 was 4.3 ng/mL, which is considerable for anestrus ewes, following PGF2α administration. The mean time to reach maximum serum P4 concentration was 5.8 h, with a mean concentration of 22.5 ng/mL. Serum P4 levels returned to basal values (T0) after 48 h. An increased P4 production rate (PR) was detected following PRG administration, which continued for 24 h. A single injection of PRG reduced the variety of serum P4 levels from 24 h onward. The two different PRG generated different serum P4 concentrations. This study indicates an unusual change in serum P4 levels in anestrus ewes following PGF2α administration. 48 h after 50 mg PRG injection, the plasma levels of P4 reached basal levels in anestrus ewes.